PENGARUH PENGOLAHAN KEDELAI MENJADI TEMPE DAN PEMASAKAN TEMPE TERHADAP KADAR ISOFLAVON (EFFECTS OF SOYBEAN PROCESSING BECOMING TEMPEH AND THE COOKING OF TEMPEH ON ISOFLAVONES LEVEL) - Diah M Utari; Rimbawan Rimbawan; Hadi Riyadi; Muhilal Muhilal; Purwantyastuti Purwantyastuti (Persagi, 2010)
ABSTRACT Background: Research over the past two decades has provided significant clinical trial and epidemiological evidence for health benefits of the consumption of soybean-based foods. A health claim indicating that high soybean consumption is associated with a lower risk of coronary heart disease (CHD). Compositions of nutrient and non-nutrient in soybean have been examination and give the contribution on lower risk of CHD especially on improve of lipid profile. Isoflavones is a non-nutrient that abundant in soybean. Tempeh is fermented soybean that popular as Indonesian traditional food and content of isoflavones is greater than soybean. Objective: to study effect of soybean processing becoming tempeh and the cooking of tempeh on isoflavones level. Methods: The samples of this study is raw tempeh and steamed tempeh. The analysis of isoflavones has used high performance liquid chromatography (HPLC). Results: During soybean processing becoming tempeh, twice boiling of soybean produce result isoflavones 47.4 percent greater than once boiling. Steaming tempeh result minimized isoflavones reduction (13.3%). Although there is no dietary recommendation for individual isoflavones, may be great benefit in increased consumption of tempeh. [Penel Gizi Makan 2010, 33(2): 148-153] Keywords: tempeh, processing, isoflavones